Importance of digital technology application in the development of professional competence of future chemistry teachers - Karmanova, A.S.; Madybekova, GM.; Kavak, N. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
This article describes the preparation of a virtual laboratory in the subject and its application during the lesson. The aim of this study is to improve the professional competence of future chemistry teachers using digital technologies. Accordingly, the subject of the study is to determine the impact of digital technologies on improving the quality of education. This study is carried out by using experimental method which is a kind of quantitative research method. In the course of the work, a study of the influence of a virtual laboratory on the quality and increase in the level of students’ knowledge in a pedagogical experiment was made. The level of students’ knowledge was determined by the formula for calculating progress. A group of students who used the virtual laboratory showed a high level of knowledge. These data prove the effectiveness of conducting laboratory classes in chemistry using a virtual laboratory, which is one of the digital technologies. The effectiveness of digital technology application in the development of professional competence of future chemistry teachers is shown: - chemical experiments were carried out using a virtual laboratory; - students had the opportunity to self-correct and understand laboratory work at re-watching; - prepared with the help of animation and color images, a virtual laboratory has increased the interest of students; - at discussion the results of the lesson, a test was conducted on the “quizizz” program; - to determine the significance of the virtual laboratory, the lesson was conducted in two groups, at analysis of the lesson results in the group where the virtual laboratory was used, the level of knowledge was high; - it can be observed that the professional competence of students (motivation, skills, knowledge) has increased.
Болашақ химия мұғалімдерінің кәсіби құзыреттілігін дамытуда цифрлық технологияны қолданудың маңызы
Значение применения цифровых технологий в развитии профессиональных компетенций будущих учителей химии
Keywords: digital technology; professional competence; virtual laboratory; informatization of education; digitalization; Macromedia Flash Player program; cations of the second analytical group; qualitative reaction; acidbase classification; analytical chemistry; chemical experiment